Let it snow three holiday romances - Green, John 1977-; Johnson, Maureen 1973-; Myracle, Lauren 1969- (New York Speak Penguin Group, 2014)
In three intertwining short stories, several high school couples experience the trials and tribulations along with the joys of romance during a Christmas Eve snowstorm in a small town
The Jubilee express / Maureen Johnson -- A cheertastic Christmas miracle / John Green -- The patron saint of pigs / Lauren Myracle
014-017
1
NEW, LITERATURE
Keywords: Christmas stories; Dating (Social customs) -- Juvenile fiction; Short stories, American; Christmas -- Fiction; Dating (social customs) -- Fiction; Interpersonal relations -- Fiction; Short stories; Storms -- Fiction; Young adult fiction